Population Dynamics, Size Hierarchies and Neighbour Interactions of Early Colonizing Vascular Plants of a Norwegian Glacier Foreland - Berg, June Susanne (2015)
The population dynamics of the three early colonizing vascular plant species Oxyria digyna, Poa alpina and Ranunculus glacialis was studied in a chronosequence in the glacier foreland of Hellstugubreen in Jotunheimen National Park in southern Norway, with particular emphasis on detecting the possible impact of intra- and interspecific competitive interactions. The first individuals were observed on terrain exposed for minimum six years. The density of these pioneer species then increased linearly, reaching a peak at a distance of 115-400 m from the glacier front, equivalent to 15-40 years of habitat exposure. Density subsequently decreased and the species disappeared in areas exposed for 65 years or more, with the exception of a few brooklet verges. The relative abundance of the species differed significantly, with O. digyna twenty times more abundant than the least abundant R. glacialis. The size frequency distributions of the species were strongly positively skewed throughout the first 21 years since deglaciation, revealing no sign of competitive interactions (e.g. self-thinning). All three species had a significant correlation between size and fertility, and in general the percentage of fertile individuals in the populations increased with time. In terrain exposed for 6-8 years the fertility of O. digyna was 22 % rising to 68 % after 17-21 years. R. glacialis had 20% fertile individuals in terrain exposed 6-8 years, rising to 35% after 17-21 years. The fertility of P. alpina rose from 35% to 65% in the same intervals. In O. digyna a significant negative correlation was found between the performance (size & fertility) of an individual plant and the size of nearest conspecific neighbour. The three pioneer species occurred mainly in sample squares with low vegetation cover value (1-10%). However, their decrease over time could not be related to a general increase in vegetation cover. The species in physically contact or sharing growth site with the pioneer species in the phase where their populations decline tend to be other pioneers rather than later successional species, but for all three species there was clear evidence of progressive substitution with Salix herbacea.